Family matters: involuntary parental unemployment during childhood and subjective well-being later in life - Milena Nikolova; Boris N. Nikolaev (Global Labor Organization (GLO), 2018)
We are the first to examine how parental unemployment experienced during early-, mid- and late-childhood affects adult life satisfaction. Using German household panel data, we find that parental unemployment induced by plant closures and experienced during early (0-5 years) and late (11-15 years) childhood leads to lower life satisfaction at ages 18-31. Nevertheless, parental unemployment can also have a positive effect depending on the age and gender of the child. Our results are robust even after controlling for local unemployment, individual and family characteristics, parental job loss expectations, financial resources, and parents' working time when growing up. These findings imply that the adverse effects associated with parental unemployment experienced at a young age tend to last well into young adulthood and are more nuanced than previously thought.
Keywords: I31; J01; J65; 330; life satisfaction; parental unemployment; company closures; life-cycle analysis; German Socio-Economic Panel